MENINGKATKAN PENGETAHUAN SAINS MELALUI PENDEKETAN EKSPLORASI LINGKUNGAN SEKITAR AUD DI PAUD GEMBOR PERTIWI BINUANG - Saniah, Eneng Sri Susilawati, Hadi Sutiawan (Jurnal Pendidikan dan Penelitian Semesta Mendidik, 2024)
The main goal to be achieved in this study is to find out the ability to recognize numbers in children in KB PAUD Al Hidayah, Pamarayan District. The subjects in this study are all 9 students in class A of KB PAUD Al-Hidayah, Pamarayan District. This type of research is a collaborative classroom action research consisting of two cycles where each cycle is carried out four meetings. The data collection techniques used are obervation and documentation. The data analysis used  is descriptive, qualitative, and quantitative. The results of the study showed that there was an increase in the ability to  recognize the number of children in group A in KB PAUD Al-Hidayah, Pamarayan District. In the implementation of the Pre-Cycle, the ability to recognize the number of children reached 33.33%, which shows that the implementation of the  Pre-Cycle is still in the criteria for starting to develop. In Cycle I, the implementation of improvement actions increased by 51.4%, which showed that the criteria developed as expected. And in Cycle II it reached 90.28%, which shows that the creteria is developing very well. Based on the results of the research above, it can be concluded that the ability to recognize the number of children in Group C of PAUD Al-Hidayah Pamarayan District through the number card method has increased.